Haematological and Biochemical Reference Values for Healthy Population of Maferinyah Rural Community in Guinea. (3rd August 2020) - Béavogui, Abdoul Habib; Touré, Almamy Amara; Camara, Daouda; Doumbouya, Abdoulaye; Sylla, Malick Minkael; Touré, Sékou; Togo, Ahmadou Hamidou; Diallo, Mamadou Saliou; Delamou, Alexandre; Sagara, Issaka; Dicko, Alassane; Djimdé, Abdoulaye
Abstract : Guinea's reference ranges for biological parameters rely on those of Caucasian values. Variability in reference ranges according to the context is well-documented. We conducted this study for the purpose of future malaria clinical trials that assess the efficacy and safety of malaria drugs. A repeated cross-sectional study was carried out, in an apparently healthy cohort population. Surveys took place in Maferinyah rural community, which is located at 75 km from the capital. The 2.5 th and 97.5 th percentiles were determined nonparametrically and stood for reference intervals. Reference values were determined separately for males and females according to ranges of age (6-10 years of age; 11-15 years of age; 16-45 years of age). Differences between genders were tested using the Mann-Whitney test, while the Friedman test was performed to test differences within each gender group according to the seasons. A total of 450 volunteers were enrolled. The median age was 13. Males 16-45 years of age had significantly higher hematologic and biochemical values compared to a female of the same age (for hematological parameters: Mean Cell Hemoglobin Concentration MCHC p ≤ 0.001, Platelets p ≤ 0.001, monocytes p = 0.0305, eosinophils p = 0.0225 ; for biochemical parameters: Aspartate aminotransferase AST p ≤ 0.001, Alanine Aminotransferase ALT p ≤ 0.001, creatinine p ≤ 0.001 ). We noticed significant seasonal variations for all the biochemical parameters and some hematologic parameters (Mean Corpuscular Hemoglobin MCH, MCHC, Mean Cell volume). This is the first study establishing hematologic and biochemical parameters in Guinea. These findings provide a useful guide for the clinical researchers and care providers. Studies on large scale and in different settings would be also desirable.